Preliminary study on the potential use of Averrhoa bilimbi L. as a supercapacitor electrode material - Rahmi, Lailatul; Awitdrus, Awitdrus (Universitas Riau, 2025)
The global energy crisis and environmental damage caused by the use of fossil fuels have driven the development of environmentally friendly energy storage technologies, one of which is the supercapacitor. This study aims to explore the potential of Averrhoa bilimbi L. (belimbing wuluh) as a source of activated carbon for supercapacitor applications. Activated carbon from belimbing wuluh pulp was synthesized through a carbonization process at 800°C. Morphological characterization using SEM showed a porous surface that had not yet developed optimally, while EDX analysis identified carbon, oxygen, and magnesium as the dominant elements. Electrochemical characterization was carried out using CV and GCD methods with variations in H2SO4 electrolyte concentration (1, 2, and 3 M). The electrode tested with 1 M showed the best performance, with a specific capacitance of 45.98 F/g (CV) and 96.81 F/g (GCD). These results indicate that belimbing wuluh has potential as a sustainable natural material for the development of environmentally friendly supercapacitors.